Highly luminous and green-emitting Eu2+ activated Eu1-xSrxAl2O4 (0 ≤ x ≤ 1) materials for NUV-LEDs - Kim, Donghyeon; Lee, Eunji; Ha, Donghwa; Lee, Jungjun; Bae, Jong Seong; Ahn, Sung Il; Chung, In; Kim, Seung Joo; Park, Jung Chul (Materials Chemistry and Physics, 2019)
Eu1-xSrxAl2O4 (0.0 ≤ x ≤ 1.0) materials were successfully synthesized and characterized. Rietveld refinements revealed that the monoclinic phase with the P21 (No. 4) space group is thermodynamically stable within the wide EuO-SrO-AlO solid-solution range. Spectroscopic refinements using infrared (IR), Raman, and X-ray photoelectron spectroscopy (XPS) indicated that the vibrational modes are somewhat chemically shifted, most likely because of the difference in reduced mass (μ) between Eu‒O and Sr–O bond. Based on the binding energies of the reference compounds (Eu2O3 and EuCl2), the predominant Eu2+ species are partially oxidized to Eu3+ species in the near-surface region. The band-gap energies (Eg) of the Eu1-xSrxAl2O4 (x = 0.0, 0.5, and 1.0) materials were determined from the Kubelka-Munk transformation of the diffuse reflectance spectra (DRS) to be 2.56, 2.59, and 4.23 eV, respectively, in agreement with previously reported values determined by theoretical band calculation. The photoluminescence (PL) and LED-emission results revealed that the luminous efficiency of the Eu0.3Sr0.7Al2O4 was approximately 2.5 times higher than that of EuAl2O4 phosphor. Using Williamson−Hall (W−H) method, the determined structural strains of phosphors revealed that the compressive strain plays an important role in the enhanced PL intensity ofthese phosphors. These materials provide a platform for developing new phosphors for application in solid-state lighting.
Keywords: Diffuse reflectance spectrum; EuAl2O4; Kubelka-Munk transformations; Near surface regions; Solid solution range; Solid state lighting; Sr substitutions; Thermodynamically stable; EuAl2O4; IR & Raman; PL & LED-Emission; Sr-substitution; XPS